RESPONSE CHARACTERISTICS OF WIND EXCITED CABLES WITH ARTIFICIAL RIVULET - GU Ming(顾明) LIU Ci-jun(刘慈军) XU You-lin(徐幼麟) XIANG Hai-fan(项海帆) (Applied mathematics and mechanics, 2002)
A wind tunnel investigation of response characteristics of cables with artificial rivulet is presented.A series of cable section models of different mass and stiffness and damping ratio were designed with artificial rivulet.They were tested in smooth flow under different wind speed and yaw angle and for different position of artificial rivulet.The measured response of cable models was then analyzed and compared with the experimental results obtained by other researchers and the existing theories for wind-induced cable vibration.The results show that the measured response of horizontal cable models with artificial rivulet could be well predicted by Den Hartog' s galloping theory when wind is normal to the cable axis.For the wind with certain yaw angles, the cable models with artificial rivulet exhibit velocity-restricted response characteristics.